Pleomorphic adenoma involving soft tissue overlying the anterior border of ramus of the mandible: A rare ectopic presentation - Naresh Kumar Sharma; Akhilesh Kumar Singh; Arun Pandey; Vishal Verma (Journal of Oral Biology and Craniofacial Research)
Ectopic pleomorphic adenoma is a rare presentation in sites other than major and minor salivary glands. In literature, cases of pleomorphic adenoma in the soft tissue of the neck, skin of the external auditory canal, subcutaneous layer of nose, and lymph node of mediastinum have been reported. We report a case of ectopic pleomorphic adenoma localized in the soft tissue over the anterior border of the ramus of left side of the mandible.